EXPLORING TEACHER'S WAYS IN UTILIZING VISUAL IMAGES IN NARRATIVE TEXT FOR EFL LOWER SECONDARY SCHOOL - Faqihudin Abdurrahman Annaser Ansas, - (2023)
Visual images offer implicit and explicit ideological message about the various ways of being, becoming, and belonging where it plays an important role in the dissemination of learners to literacy practices (Stephens, 1992, Mills and Exley, 2014). In Indonesian EFL context, the development of visual narrative using visual images can lead the students through the process of viewing images in a critical way and how they participate in that active process. From several studies however, English teachers are still hesitant to explore the visual images provided in textbooks or other learning resources. Therefore, this study intended to investigate how teacher utilize visual images in narrative text to support the notion of visual literacy in EFL classroom using Hattwig et al. (2013) framework of image interpretation. The study found that the teacher implemented still images, moving images, and online websites to teach narrative text by paying attention to visual elements that can help students understand the materials. However, there are some visual aspects that make the teacher less optimal in conveying the meaning of an image, for example from the context where there are images that are less relevant to the setting of the story. Gambar visual menampilkan makna ideologis secara implisit dan eksplisit mengenai berbagai cara dalam memahami rasa keberadaan dan rasa memiliki di mana hal tersebut memainkan peran penting dalam penyebaran peserta didik ke praktik literasi (Stephens, 1992, Mills and Exley, 2014). Dalam konteks EFL di Indonesia, pengembangan narasi visual menggunakan gambar visual dapat menuntun siswa melalui proses melihat gambar secara kritis dan bagaimana mereka berpartisipasi dalam proses aktif tersebut. Namun, dari beberapa penelitian, guru bahasa Inggris masih ragu untuk mengeksplorasi gambar visual yang disediakan dalam buku teks atau sumber belajar lainnya. Oleh karena itu, penelitian ini bermaksud untuk menyelidiki bagaimana guru memanfaatkan gambar visual dalam teks naratif untuk mendukung gagasan literasi visual di kelas EFL menggunakan kerangka interpretasi gambar Hattwig et al. (2013). Studi ini menemukan bahwa guru menerapkan gambar diam, gambar bergerak, dan situs web online untuk mengajarkan teks naratif dengan memperhatikan elemen visual yang dapat membantu siswa memahami materi. Namun, ada beberapa aspek visual yang membuat guru kurang optimal dalam menyampaikan makna sebuah gambar, misalnya dari konteks dimana terdapat gambar yang kurang relevan dengan latar cerita.